Thermal performance of a heat pipe with two dissimilar condensers for a minimum-temperature thermal storage system. - Park, Min Kyu
An experimental study was conducted to investigate the thermal performance of a heat pipe having two dissimilar condenser sections which were subject to different boundary conditions. The first condenser dissipated heat to the surrounding air through annular fins by natural convection, while the second one was cooled by a liquid by forced convection at different temperatures. The container and the wick were made of stainless steel and the working fluid was Dowtherm-A, which is used for medium temperature applications. The diameter and length of the heat pipe were 25.4 mm and 1 m, respectively. The maximum thermal load was 1 kW and the operating temperature of the heat pipe was around 250 degree celcius. The liquid fill charge was adjusted so that the first condenser section might work as an evaporator when the original evaporator was inactive in a vertical configuration. The experimental results were analyzed in terms of thermal resistance and effective thermal conductivity against input heat flux and operating temperature.
Keywords: Heat pipe; Medium High Temperature; Dissimilar Condensers; Experiment